BEHAVIOR MODEL OF ADOPTION OF ONLINE INFORMATION SYSTEM TECHNOLOGY - Rahim Matondang, Nazaruddin Matondang, Sanco Simanullang, Harmein Nasution (International Journal of Advanced Science and Technology, 2020)
This study discusses the extent to which the adoption of the Corporate Reporting Information System (SIPP) is specifically for companies participating in BPJS Employment. SIPP Online is a website-based application that can be run using an internet connection for all BPJS Employment companies. The company (HR and Payroll) can take advantage of the SIPP Online application in employment reporting every month online. Data analysis was performed using Partial Least Square (PLS) in the model and hypothesis testing. The results of the study indicate that the independent / exogenous variables have contributed to the acceptance of the SIPP Online application.